Race, class and the equity dilemma : examining the usefulness of a biographical questionnaire in identifying Resilient-Agency (R-A) to supplement admission criteria into the University of Pretoria - Bezuidenhout, Andries (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2018.